The Influence of Social Media Marketing Instagram on Purchase Intention in Batik Lanang Wadon Ponorogo - Ririn Dwi Puspitasari; Fery Setiawan; Eka Destriyanto Pristi Ayuningtyas (IAEI, 2025)
This study aims to determine the effect of e-WOM, Responsiveness, and Trendiness on Purchase Intention in Batik Lanang Wadon Ponorogo. The population in this study were all Instagram users who followed the Batik Lanang Wadon Instagram account. Sampling technique with accidental sampling technique. Determination of sample size using Hair's formula and obtained as many as 150 samples on consumers or potential consumers who are followers of Instagram social media Batik Lanang Wadon Ponorogo. The results showed that the e-WOM variable had a positive and significant effect on the Purchase Intention of Batik Lanang Wadon Ponorogo, Responsiveness had a positive and significant effect on the Purchase Intention of Batik Lanang Wadon Ponorogo, and Trendiness had a positive and significant effect on the Purchase Intention of Batik Lanang Wadon Ponorogo.